Data Offloading Over Vehicular DTNs: City-Wide Feasibility Study in Nagoya - Takamasa Higuchi; Lei Zhong; Ryokichi Onishi (IEEE Open Journal of Vehicular Technology)
The increasing network traffic from connected vehicles is putting a strain on the limited bandwidth resources of cellular networks. Delay-tolerant networking (DTN) over vehicle-to-vehicle (V2V) communications has been considered as an effective means of offloading the cellular data traffic, while its quantitative performance in urban road traffic remains unclear in many aspects. In this paper, we unveil the benefits of data offloading over vehicular DTNs by city-scale network simulations in Nagoya, Japan. The simulation scenario embraces more than 8 million vehicle trips over five consecutive days. The vehicle routes are carefully calibrated against public statistics on the road traffic volume to enable realistic simulations of V2V communication opportunities between vehicles on the road. The results indicate the strong potential of vehicular DTNs in mixed urban road traffic, comprised of both public transport and privately owned vehicles – a large amount data traffic can be offloaded from cellular networks to V2V communication networks even with the limited ratio of vehicles participating the vehicular DTNs.